The Phenomenon of demonstrations in the Arab countries and their social dimensions - Tahri , Lakhdar Ben Laid (Social Empowerment Journal, 2020)
This study aims To identifythe factors and causesThat lie behindthe outbreakof demonstrations and protests thatbroke outand sweptMany Arab countriesDuring the years 2018 and 2019, As a natural reaction to the suffering of the Arab peoples from the oppression of their rulersIn addition to That, it deals with the repercussions of the demonstrations in the Arab countries. The researcher has used the descriptive analytical method in reviewing the concept ofprotests and demonstrations, as this method is appropriate for answering the study questions. He study concluded that Arab demonstrations and protests has been found as a result of the procedure of the repressive Arab regimes toward its peoples ,It has affected all the political, economic andsocial aspects of life.